Environmental imprints of landscape evolution and human activities during the Holocene in a small catchment of the Calanques Massif (Cassis, southern France). (September 2015) - Romey, Carole; Vella, Claude; Rochette, Pierre; Andrieu-Ponel, Valérie; Magnin, Fréderic; Veron, Alain; Talon, Brigitte; Landuré, Corinne; D'Ovidio, Anne-Marie; Delanghe, Doriane; Ghilardi, Matthieu; Angeletti, Bernard
This paper is based on a multidisciplinary study using both paleoenvironmental methods (biological, sedimentological, magnetic and geochemical) and archaeological data in order to characterize landscape and hydrological network changes as well as human impact on a littoral catchment in the Western Mediterranean area. Sedimentary records obtained around a coastal alluvial plain (Cassis, Southeastern France) reveal local environmental changes and human activities since the Neolithic (ca. 6000 cal. BP). Anthropogenic impact is already noticeable in the earliest record, and we follow its evolution through time. According to biological markers, the Holocene landscape of the Calanques is dominated by a mosaic of open herbaceous formations partly generated by human activity. The prevalence of Cernuella virgata in malacofauna successions and of coprophilous fungal spores in the pollen record testifies to the spread of agro-pastoral activities. Two increases of anthropogenic impact are highlighted during the Roman (ca. 2000 cal. BP) and Modern (from ca. 1450 to today) periods. Lead isotope analyses indicate an anthropogenic release of lead, possibly originating from the Greek Cyclades (ca. 2000 cal. BP). Hydrographic and agricultural work is also enhanced during the Roman period. Magnetic parameters and lead isotopes indicate that the Modern anthropogenic impact may be associated with high temperature activities (e.g. lime kiln, fossil fuel).